Read my LIPSS: organic lasers on micromachined resonators - Tiange Dong; Tobias Antrack; Frithjof Pietsch; Jakob Lindenthal; Markus Löffler; Bernd Rellinghaus; Johannes Benduhn; Markas Sudzius; Karl Leo (Nature Communications)
Abstract Thin-film lasers based on organic semiconductors offer significant potential for miniaturized sensing and optical memory. We present a new method for creating first-order distributed feedback (DFB) Bragg gratings using laser-induced periodic surface structures (LIPSS) as the optical resonator. These subwavelength structures, fabricated via femtosecond laser micromachining, exhibit stable periodicities and provide sufficient feedback for lasing in an Alq3:DCM film. The laser emission wavelength can be widely tuned by varying the LIPSS periodicity defined by the pulse spacing of the structuring laser. While lasing is limited by LIPSS imperfections, we demonstrate that individual LIPSS gratings optically couple into a coherent macroscopic supermode. This coupling dramatically increases lasing efficiency and reduces thresholds by two orders of magnitude compared to a single LIPSS element. This straightforward fabrication enables solid-state organic DFB lasers as integrated, on-chip coherent light sources, eliminating complex external coupling into photonic circuits.